We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
287
1
avatar

Let f(x) = 3x-8 and g(f(x)) = 2x^2 + 5x - 3. Find g(-5).

 Feb 8, 2018

Best Answer 

 #1
avatar+8780 
+3

f(x)  =  3x - 8

 

Let's find what value of  x  makes  f(x)  be  -5 .

 

3x - 8   =   -5

3x   =   -5 + 8

3x   =   3

  x   =   1

 

When   x  =  1   ,  f(x)  is  -5 . That is,  f(1)  =  -5 .

 

g( f(x) )  =  2x2 + 5x - 3

g( f(1) )  =  2(1)2 + 5(1) - 3

g(  -5  )  =  2(1)2 + 5(1) - 3

g(  -5  )  =  2(1) + 5(1) - 3

g(  -5  )  =  2 + 5 - 3

g(  -5  )  =  4

 Feb 8, 2018
 #1
avatar+8780 
+3
Best Answer

f(x)  =  3x - 8

 

Let's find what value of  x  makes  f(x)  be  -5 .

 

3x - 8   =   -5

3x   =   -5 + 8

3x   =   3

  x   =   1

 

When   x  =  1   ,  f(x)  is  -5 . That is,  f(1)  =  -5 .

 

g( f(x) )  =  2x2 + 5x - 3

g( f(1) )  =  2(1)2 + 5(1) - 3

g(  -5  )  =  2(1)2 + 5(1) - 3

g(  -5  )  =  2(1) + 5(1) - 3

g(  -5  )  =  2 + 5 - 3

g(  -5  )  =  4

hectictar Feb 8, 2018

25 Online Users

avatar
avatar